1986
DOI: 10.1016/s0022-5347(17)45934-9
|View full text |Cite
|
Sign up to set email alerts
|

Operative Recovery of Vasal Sperm From Anejaculatory Men: Preliminary Report

Abstract: Sperm showing good motility and function, as demonstrated by the in vitro sperm penetration assay using hamster ova, were collected from the vas deferens of 3 men with ejaculatory failure. The collection procedure may be repeated over multiple ovulatory cycles. The sperm may be used to attempt artificial insemination or in vitro fertilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…Surgical procedures for sperm retrieval include the testicular sperm extraction (TESE) and epididymal or vas deferens spermatozoal aspiration. Some authors have reported successful sperm retrieval from the vas deferens (Chen et al, 1998) and from implanted sperm reservoirs in SCI men (Berger et al, 1986;Brindley et al, 1986;Bustillo & Rajfer, 1986;Macourt et al, 1991). The sperm recovery rate from SCI men ranges from 86% to 100% Hirsh et al, 1993;Dahlberg et al, 1995;Lochner-Ernst et al, 1997).…”
Section: Surgical Techniques For Sperm Recoverymentioning
confidence: 99%
“…Surgical procedures for sperm retrieval include the testicular sperm extraction (TESE) and epididymal or vas deferens spermatozoal aspiration. Some authors have reported successful sperm retrieval from the vas deferens (Chen et al, 1998) and from implanted sperm reservoirs in SCI men (Berger et al, 1986;Brindley et al, 1986;Bustillo & Rajfer, 1986;Macourt et al, 1991). The sperm recovery rate from SCI men ranges from 86% to 100% Hirsh et al, 1993;Dahlberg et al, 1995;Lochner-Ernst et al, 1997).…”
Section: Surgical Techniques For Sperm Recoverymentioning
confidence: 99%
“…(9) BERGER, BRINDLEY et BUSTILLO 6tendent les indications du prtl~vement dtftrentiel aux antjaculations et 6jaculations rttrogrades rebelles au traitement classique. (1,3,4). Deux grossesses sont obtenues dans la strie de Brindley ; la premiere dans le cadre d'une antjaculation, la seconde dans le cadre d'une s16nose dtftrentielle bila16rale.…”
Section: Discussionunclassified
“…Because it has been suggested that a suspension of fresh spermatozoa in tissue culture medium is more likely to achieve fer- (1984) described an expanded polytetrafluoroethylene spermatocele and have recovered spermatozoa, but they lacked motility. Berger et al (1986) described the operative recovery of motile spermatozoa by repeated vasotomy but have yet to report a pregnancy.…”
Section: Discussionmentioning
confidence: 99%